THE DRAWING OF 3-YEARS OLD CHILDREN AND THEIR ARTICULATION WITH THE RUDIMENTS OF WRITING - Escudeiro, Cristiane Moraes; Barbosa, Eliza Maria [UNESP]; Silva, Jana-Na Cassiano (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2016)
This article describes and analyzes the construction of a didactic sequence used to ensure the development of the body image, carried out with children aged three to four years old, who attend a public Early Childhood Education in Araraquara. We defend the point of view that this stage of basic education although does not have as main function consolidate the literacy process can offer a unique contribution to this process as we conceive it as the result of a process that articulates gestures, spoken language, drawing and writing, in a collective and cultural construction trajectory. The presuppositions of Cultural-Historical Psychology and Historical-Critical Pedagogy subsidize the discussion. Based on this approach, we seek references to defend the drawing as one of the exclusively human ways to represent reality, turning it as teaching significant content. To defend it as a teaching content and build a didactic sequence to allow its further development we reiterate the humanizing role of formal education as defined by Historical-Critical Pedagogy. The results of sequence execution indicate an advance in the graphic expressions of children and support the conception of early childhood education as a context of consolidation, in contemporary times, of the maximum possibilities of children as generic humans.
Keywords: Drawing; Early childhood education; Historical-critical pedagogy; Cultural-historical psychology; Literacy